Implications of Indonesia's joining the BRICS on national defense and security strategy - Edy Triharyono; Yenglis Dongche Damanik; Ghazalie Ghazalie (Goodwood Publishing, 2025)
Purpose: This study analyzes the strategic implications of Indonesia’s membership in BRICS on national defense and security, focusing on its potential to strengthen military cooperation, diversify defense procurement, and enhance geopolitical positioning while navigating complex global alignments. Research methodology: This study employs a qualitative method using a literature review and secondary data analysis. These sources include policy documents from the Indonesian government, international reports, and academic publications related to BRICS, defense diplomacy, and global security dynamics. Descriptive and comparative analysis techniques were used to explore the strategic implications and potential shifts in Indonesia's foreign policy. Results: The study finds that BRICS membership offers Indonesia enhanced access to alternative funding via the New Development Bank, broader defense cooperation, and opportunities to modernize military capabilities through technology transfer. It also provides a platform for more assertive defense diplomacy. However, risks include potential diplomatic friction with Western allies, internal power asymmetries within BRICS countries, and challenges to Indonesia’s non-aligned foreign policy stance. Conclusions: Indonesia’s BRICS membership can bolster national defense and strategic autonomy if managed with diplomatic prudence. A balanced foreign policy is essential to leverage the advantages of BRICS while preserving partnerships with Western powers and ASEAN allies. Investment in cybersecurity, military modernization, and defense diplomacy is crucial for long-term stability. Limitations: This study relies solely on secondary data, limiting insights into internal policy dynamics and practical implementation. Contribution: It offers a strategic perspective on Indonesia’s BRICS engagement and its implications for defense diplomacy and national security.